Aid and Institutions: Local Effects of World Bank Aid on Perceived Institutional Quality in Africa - Ann-Sofie Isaksson; Dick Durevall (Research Institute of Industrial Economics (IFN), 2021)
Motivated by the lack of sub-national empirical evidence on the relationship between aid and institutional development, this study explores the local effects of World Bank aid on perceived institutional quality in African aid receiving countries. We combine geo-referenced data on the subnational allocation of World Bank aid projects to Africa over the 1995-2014 period with geo-coded survey data for 73,640 respondents across 12 Sub-Saharan African countries. To account for the endogenous placement of World Bank project sites, we compare the estimated effect of living near a site where a World Bank project was under implementation or completed at the time of the interview, to that of living near a site where we know that a World Bank project appeared after the survey date. The empirical results suggest a positive impact of World Bank aid on perceived institutional quality, as measured by citizens' expressed willingness to abide by key formal institutions. This applies even if we consider overall World Bank aid, i.e. not just projects specifically targeted at institutional development. As may be expected, however, the estimated effects are more pronounced when restricting our attention to projects focusing on institution building. Notably, the observed effects concern finalized projects, not projects still under implementation, highlighting that institutional change is a slow process.
Keywords: F35; O17; O19; O55; 330; Aid; Institutions; Africa